Chemical Waste Management And Recycling Optimization Using Iot-Enabled Systems - Gupta, Anirudh; Shukla, Mahimna (Journal of Neonatal Surgery, 2026)
Background: This requires substantial support and resources in chemical waste management and recycling, such as automated technology, chemical data management systems, advanced materials, etc. The growing need for efficiency and sustainability in waste management systems is leading industries to adopt IoT-based applications in monitoring and optimizing chemical waste disposal and recycling systems. For instance, IoT-based techniques are adding real-time tracking, automated segregation, and predictive analytics, which can help make waste management much more efficient. Despite their benefits, myriad challenges remain to the adoption of IoT-enabled systems, including high implementation costs, regulatory inconsistencies, technical expertise gaps, and data security concerns. Tackling these issues is essential to improving waste management practices, ensuring compliance with regulations, and promoting environmental sustainability. Aim: The current paper investigates the trends, problems, and future directions in chemical waste management and recycling optimization with IoT-based approaches. It specifically explores the knowledge, level of use, and perceived effectiveness of IoT-based waste management systems, where it also aims to determine whether there are barriers and factors that influence the widespread implementation of IoT-based waste management systems. The findings of the study will inform the industries, policymakers, and the environmental agencies to encourage or accelerate the adoption of the IoT in waste management and propel the sustainable waste disposed of solutions. Methodology: Based on structured survey interviews with 110 respondents, including representatives from chemical industries, waste management companies, environmental non-government organizations, government agencies, and academic researchers. The study employed a cross-sectional mixed-methods design, integrating both quantitative and qualitative data for a comprehensive evaluation of IoT implementation in chemical waste management. Descriptive and inferential statistical analyses were used to assess awareness levels, adoption rates, challenges, and perceived benefits of IoT-assisted waste management. In order to position the findings in the context of existing literature, a systematic literature review was also conducted focusing on smart waste tracking, hazardous waste management, and IoT use cases for sustainability. Findings: The paper provides important insights to characterize the status of IoT-enabled waste management by finding out the awareness level about the IoT-based waste management along with its adoption barriers. While 58% of the respondents were aware of IoT-enabled waste tracking, only 30% had implemented IoT within their organizations. According to the report, regulatory compliance requirements (50%), cost efficiency (45%), and sustainability goals (40%) were the primary factors driving IoT adoption in waste management. The most important barriers identified were high implementation costs (50%), lack of technical expertise (40%), and concerns around data privacy and security (35%). Respondents believed that 55% of respondents said government incentives like grants and standard regulatory frameworks (48%) would greatly increase adoption rates. Conclusion: But to facilitate broader adoption, we need to solve for the cost, technical and regulatory challenges. The results underscore the role of tailored financial motivations, supportive government laws, and sectoraliszied training initiatives in adopting the use of IoT in waste management. Further work can address cost-benefit analysis, case studies in paradigm shift in implementing IoT-based systems and frameworks on secure, scalable and smart waste management. Transforming chemical waste management into a smart and eco-friendly system will require collaboration across sectors, between industries, policymakers, and technology providers